Asociación entre la escala de resultados de Glasgow con el sistema de puntuación tomográfica de Rotterdam en pacientes con traumatismo craneoencefálico moderado a severo en el Hospital Regional de Loreto del 2018-2021 - Asío Macedo, Kenji Alexander (2023)
Objective: To determine the association between the Glasgow Outcome Scale and the Rotterdam Tomographic Scoring System in patients with moderate to severe head trauma at the Loreto Regional Hospital from 2018-2021. Materials and methods: A retrospective, cross-sectional observational study was conducted in patients with moderate to severe head trauma. Results: 106 patients were analyzed. The distribution of patients (%) for the Glasgow results scale was: for GOS1 60.4%, for GOS2 13.2%, for GOS3 15.1%, for GOS4 1.9% and for GOS5 9.4%. The distribution of patients (%) for the Rotterdam score was: for Rotterdam1 3.2%, for Rotterdam2 50.9%, for Rotterdam3 21.7%, for Rotterdam4 7.5%, for Rotterdam5 4.7 % and for Rotterdam6 1.9%. The distribution of patients (%) for the tomographic findings was: 21.7% showed deviation from the midline, 19.9% presented compressed or absent basal cisterns, the predominant mass lesion was intracerebral hematoma with 47.2 %, subarachnoid hemorrhage was present in 27% and intraventricular hemorrhage in 3%. A significant association was found between the Glasgow Outcome Scale and the Rotterdam Tomographic Scoring System (p = 0.000). Conclusion: This determines that there is an association between the Glasgow Outcome Scale and the Rotterdam Tomography Scoring System in patients with moderate to severe head injury.